Investigation into the effects of Trypanosoma congolense infections on the pharmacokinetics of Homidium in Boran cattle - Murilla, G.; Peregrine, A.S.; Holmes, P.H.; Eisler, M.C.; Ndung'u, J.M. (OAU/STRC, 1999)
Control of trypanosomosis in cattle, sheep and goats in endemic areas has depended largely on the use of chemotherapeutic or chemoprophylactic agents. One such agent is homidium. The normal use of homidium has been in the treatment of infections due to both Trypanosoma congolense and T. vivax in cattle, sheep and goats at the recommended dose rate of 1.0 mg kg -1 b.w. This paper describes the results of an investigation into the chemotherapeutic activity of homidium against t. congolense infections in cattle. Two groups of five Boran cattle were infected with two populations of T. congolense; one drug-sensitive IL 1180) and one drug-resistant (IL 3330). Parasitaemia was estimated using the methods of Murray et al. (1977); the serum drug levels by the method described by Murilla (1996) and the pharmacokinetic parameters using the formulae described by Baggot (1977). After infection, there was a rapid drop in packed cell volume (PCV) values from a mean pre-infection value of approximately 40 percent to approximately 25 percent within 14 days of infection in cattle infected with IL 1180. However, in cattle infected with IL 3330, the drop in PCV was more gradual from approximately 40 percent to approximately 30 percent within the same period of time. The animals were treated with homidium bromide at a dose rate of 1.0 mg kg -1 body weight (b.w.) seven days after the last animal in each group was detected positive. Following intramuscular (i.m.) treatment of cattle infected with drug-sensitive trypanosomes, no parasites were detected in the bloodstream of four out of five cattle within 24 hours; the fifth within 48 hours. During this period and for the next 10 days after treatment, an acceleration in the rate of drug elimination was observed. Thereafter, the rate of elimination reverted back to that observed in non-infected cattle (Murilla, 1996). This was accompanied by an elevation in PCV to pre-infection values. The animals remained aparasitaemic up to the end of the 90 days observation period with low serum drug concentrations of between 0.1 and 0.3 ng ml-1 in circulation.